A Phenomenological Study of the Lapindo Mudflow as a Resource for Earth Layers Learning to Enhance Elementary Students' Conceptual Understanding - Shafira Rizky Sukma Darmayanti; Nuriman Nuriman; Arik Aguk Wardoyo; Zidni Alfian Barif; Nabila Ariiqah (Universitas Syiah Kuala, 2026)
Science education in elementary schools faces various challenges, such as insufficiently contextualized learning, which results in low conceptual understanding among students. This study aimed to develop and evaluate phenomenology-based teaching materials integrating the Lapindo mudflow phenomenon for teaching earth-layer concepts in elementary schools. The study employed a research and development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product was a contextual textbook designed for sixth-grade elementary school students. The participants were 18 sixth-grade students from SDN Balongdowo, Sidoarjo, East Java, Indonesia. Data were collected through observations, interviews, validation sheets, student response questionnaires, and learning achievement tests. The validity of the teaching materials was assessed by experts, while practicality and effectiveness were evaluated through student responses and learning outcomes. The results showed that the developed teaching materials achieved a validity score of 87.14%, indicating that they were highly feasible for use in learning. The practicality test yielded a score of 90.27%, demonstrating that the materials were easy to use, attractive, and helpful in supporting students’ understanding. Furthermore, the effectiveness test revealed a mastery learning rate of 83.3%, indicating that the teaching materials effectively improved students’ comprehension of earth-layer concepts. These findings suggest that integrating the Lapindo mudflow phenomenon into science instruction can provide meaningful contextual learning experiences and enhance conceptual understanding among elementary school students. Therefore, the developed teaching materials can serve as an effective alternative learning resource for implementing contextual science education in elementary schools